2022
DOI: 10.1101/2022.11.20.517276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Costs and economic impacts of expanding marine protected area systems to 30%

Abstract: International proposals for marine biodiversity seek to expand marine protected area (MPA) coverage from 8% to 30%, known as 30x30. Quadrupling MPA coverage implies considerably higher MPA system costs and governments need early knowledge of these to inform debate. Ambitious MPA expansion also implies large potential losses or "opportunity costs" for fishers, putting pressure on governments to compromise and permit some fishing inside protected areas (a mixed high/low protection system). Crafting a balanced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Dynamics may shift depending on the circumstances and it is important to understand the drivers of these dynamical shifts so that planners can make decisions that are robust to future changes. Other land use studies assess multiple impact metrics without explicitly accounting for future uncertainty (Kroll et al., 2019; van Vuuren et al., 2015) or assess economic (Waldron et al., 2020) or environmental (Borrelli et al., 2020; Mouratiadou et al., 2016) impacts under uncertainty, but few studies implement all of these elements (Gao & Bryan, 2017). Considering only one metric may lead to myopic decisions and high regret, whereas failing to account for uncertainty can lead to decisions that leave the population vulnerable to high losses (Reckhow, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamics may shift depending on the circumstances and it is important to understand the drivers of these dynamical shifts so that planners can make decisions that are robust to future changes. Other land use studies assess multiple impact metrics without explicitly accounting for future uncertainty (Kroll et al., 2019; van Vuuren et al., 2015) or assess economic (Waldron et al., 2020) or environmental (Borrelli et al., 2020; Mouratiadou et al., 2016) impacts under uncertainty, but few studies implement all of these elements (Gao & Bryan, 2017). Considering only one metric may lead to myopic decisions and high regret, whereas failing to account for uncertainty can lead to decisions that leave the population vulnerable to high losses (Reckhow, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These impacts were highly regionally dependent, but were often positive if the protected areas were co‐managed by the state and local community and if the conservation program maintained cultural and livelihood benefits (e.g., by allowing the sustainable use of natural resources for subsistence farming). At the global scale, a comprehensive economic impact study led by the International Institute for Applied Systems Analysis found net benefits from protecting 30% of land on Earth (Waldron et al., 2020). While this study incorporated uncertainty by simulating a range of conservation scenarios in four separate general equilibrium models, a research gap exists in the conservation literature of studying socioeconomic and environmental uncertainties and their impacts on metrics of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The economic value created annually through ecosystem services is estimated at USD44 trillion (Deutz et al, 2020). According to Waldron et al (2020), ecosystem services value could be expanded by an additional USD64 billion to USD454 billion by expanding earth's protected areas from current levels to 30% of global surface area.…”
Section: The Gap At the Biodiversity And Finance Nexusmentioning
confidence: 99%
“…Interventions often seek climate, conservation or development goals aiming to mitigate climatic and ecological damages, restore past losses or deliver to human needs (Adams et al, 2004;Convention on Biological Diversity, 2022;Mansourian et al, 2017;Otero et al, 2020;Reed, Oldekop, et al, 2020). Climate, conservation and development intervention targets such as 30 by 30 indicate the intended doubling-up of such site-level efforts (Convention on Biological Diversity, 2022; Dinerstein et al, 2017;Waldron et al, 2020;Wilson, 2016).…”
Section: Introductionmentioning
confidence: 99%